Epigonus exodon, a new species of deepwater cardinalfish (Teleostei: Perciformes: Epigonidae) from Réunion, western Indian Ocean - Okamoto, Makoto; Motomura, Hiroyuki (Zootaxa, 2012)
A new species of deepwater cardinalfish, Epigonus exodon, is described based on two specimens, 97.0–60.2 mm standardlength, from Réunion (depth 450–480 m), western Indian Ocean. Epigonus exodon belongs the Epigonus oligolepis group,defined as having seven spines on the first dorsal fin, one spine and 10 soft rays on the second dorsal fin, 35–37 poredlateral-line scales to the end of the hypural and lacking an opercular spine and ribs on the last abdominal vertebra. It differsfrom other members of the group in having a narrow tongue, a shallow V-shaped tooth patch on rear two-thirds of tongue, anteriorly projecting teeth on each side of the symphysis of lower jaw, and 26–28 total gill rakers.